Determination of the optimum thickness of some moderators for fast neutrons. - Rasheed Yousif; Khalid Ismaeel (College of Education for Pure Sciences, 2009)
Abstract The study aims to determine the optimum thickness for some moderators which are used for obtaining thermal neutrons and for wide range of neutron energy (0.03 - 15 × 106) eV. The study involves two groups of materials: the first group consisted of H2O, D2O, Be, & C), while the second one are made of hydrocarbon materials (C25H52, C6H10O5, C6H12O6, C28H48O2, C18H34O2, C5H10O2, & Tissue equivalent material). The results revealed that the best moderator in the first group was water as it has a large scattering macroscopic cross section ∑)s), absorption macroscopic cross section (∑a) and it contains a high percentage of Hydrogen and that the lowest moderator within the same group is Graphite (c) since it has a higher diffusion coefficient (D), and also has a higher diffusion length (L). In the second group, it was found the best moderator was (C25H52), and the lowest one is (C6H10O5), for the same reasons mentioned above. Besides, that a lot of physical parameters are calculated which are related to neutron diffusion in the second group materials, such as (∑a), (∑s), (D), (L), (H%), (ξ), and molecular weight (M) for the hydrocarbon compounds.